Ethnic Self-Consciousness of Students and its Development in the Process of Studying the Discipline «Theory and Methods of Ethnocultural Education» - Marina P. Kamaeva (Publishing house "Sreda", 2021)
The article examines the problems of the formation of ethnic self-awareness of university students in the process of teaching the discipline «Theory and methods of ethnocultural education». The relevance of the study is determined by the state policy that elevates culture to the rank of national priorities and recognizes it as the most important factor in the harmonization of public relations, the guarantor of the preservation of a single cultural space and territorial integrity. The purpose of the article is to consider the issues of content-methodological and educational plan in the formation and development of ethnic self-consciousness of students of higher educational institutions in the process of teaching the dissertation "Theory and methodology of ethno-cultural education". The analysis of normative-legal and legislative acts in the field of culture and education, observation, and the method of generalization of pedagogical experience allowed us to identify effective forms and means of ethno-cultural education of students. The data of a sociological survey conducted before and after studying the discipline "Theory and methodology of ethno-cultural education" among students of the training direction "Folk Art Culture" of the Chuvash State Institute of Culture and Arts are presented in the article. Based on the data obtained by such criteria as the level of formation of ethnonigilism, ethnic indifference, positive ethnic identity, ethno-egoism, ethno-isolationism, ethno-fanaticism, conclusions were drawn about the positive result of the study and recommendations were made for the development of ethnic self-knowledge of students in the course of studying the discipline "Theory and Methodology of ethno-cultural education".